2022
DOI: 10.1021/acs.molpharmaceut.1c00934
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Steric Shield on Biocompatibility and Antithrombotic Activity of Dendritic Polyphosphate Inhibitor

Abstract: The polyanion, inorganic polyphosphate (polyP), is a procoagulant molecule which has become a promising therapeutic target in the development of antithrombotics. Neutralizing polyP's prothrombotic activity using polycationic inhibitors is one of the viable strategies to design new polyP inhibitors. However, in this approach, a fine balance between the electrostatic interaction of polyP and the inhibitor is needed. Any unprotected polycations are known to interact with negatively charged blood components, poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Putative cationic binding group structures described in the literature were screened for their amine pK a values, charge spacing, and linker chemistry, which may affect their flexibility. Embedding such charge switching cationic binding groups within a biocompatible scaffold known to prevent non-specific interactions resulted in a library of polycations with low charge density in their unbound state, particularly as compared to other polycation inhibitors of polyP 25 , 32 , 33 , 63 . When compared to larger polyanionic macromolecules with lower charge density, the unique features of the MPI’s scaffold serve to improve biocompatibility, presumably (at least in part) by limiting nonspecific interactions through the steric repulsion created by the PEG corona (brush layer) on the surface of the MPI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative cationic binding group structures described in the literature were screened for their amine pK a values, charge spacing, and linker chemistry, which may affect their flexibility. Embedding such charge switching cationic binding groups within a biocompatible scaffold known to prevent non-specific interactions resulted in a library of polycations with low charge density in their unbound state, particularly as compared to other polycation inhibitors of polyP 25 , 32 , 33 , 63 . When compared to larger polyanionic macromolecules with lower charge density, the unique features of the MPI’s scaffold serve to improve biocompatibility, presumably (at least in part) by limiting nonspecific interactions through the steric repulsion created by the PEG corona (brush layer) on the surface of the MPI.…”
Section: Discussionmentioning
confidence: 99%
“…For this assay, we followed a recent report from our group 63 . Detailed procedure is given in the supplementary methods.…”
Section: Methodsmentioning
confidence: 99%
“…58 Termed UHRAs (for universal heparin reversal agents), they were designed with cationic-binding groups based on tertiary amines (reasoning that they would be less toxic than primary amines) within the core of a dendritic polymer, shielded from nonspecific interactions with blood components using a protective short-chain layer of polyethylene glycol. We subsequently reported that certain members of this UHRA family are potent polyP inhibitors, and in fact two of these compounds (UHRA-9 and UHRA-10) were potent polyP blockers in vitro 59 and protected against experimentally induced thrombosis in vivo in mice. 60 These agents had significantly less bleeding risk compared with a therapeutically equivalent dose of heparin, but nonetheless at high doses they were mildly anticoagulant in vitro and caused some bleeding sideeffects in vivo via an unknown mechanism.…”
Section: Polyp As An Antithrombotic Targetmentioning
confidence: 99%
“…12,151 Thus, the design of potent polycationic PolyP inhibitors with good biocompatibility remains challenging. 152 Smith et al studied a series of polycationic polymers as PolyP inhibitors, and discovered that low molecular weight polyethyleneimine (LMW-PEI) exhibited the highest efficiency in inactivating the procoagulant effect of PolyP in vitro. 12 In a thrombotic mouse model, all tested PolyP inhibitors prolonged the time of vascular occlusion.…”
Section: Neutralizing Polyp By Positively Charged Agentsmentioning
confidence: 99%
“…160 For instance, conjugating PAMAM dendrimers and polyethyleneimine with PEG-750 achieved enhanced biocompatibility, leading to sterically shielded PolyP inhibitors. 152 However, the above-mentioned polycations all exhibit certain toxicity and bleeding risks. In 2023, Jayachandran and his colleagues reported a design concept towards inhibiting PolyP, termed macromolecular polyanion inhibitors (MPI) (Fig.…”
Section: Neutralizing Polyp By Positively Charged Agentsmentioning
confidence: 99%